Investigation the effects of friction stir processing on microstructure and mechanical properties of Al–Cu alloy fabricated by wire arc additive manufacturing - Li Liu; Wanghui Xu; Yu Li; Ruizhe Liu; Ruiwei Liu; Yongxian Huang; Chunlin Dong (Journal of Materials Research and Technology)
In this study, a hybrid additive manufacturing (AM) process that combines interlayer friction stir processing (FSP) with wire arc additive manufacturing (WAAM) is proposed to address the problems of high porosity, coarse grains, and low mechanical properties encountered in WAAM Al alloys. Straight walls of Al–Cu alloy were prepared using Er2319 wire and interlayer FSP was conducted to tailor the microstructure of deposited layers. The effects of interlayer FSP on the microstructure and mechanical properties of WAAM Al–Cu alloy was analyzed. Results show that the pore characteristics vary at different regions on the cross-section of the deposited walls. The interlayer FSP can partially repair pores by violent stirring action and downward force from FSP tool, and thereby decreases the pore size, pore density and pore area fraction of the WAAM Al–Cu alloy. Additionally, the interlayer FSP can significantly refine grains, resulting in a wider fine grain region in the WAAM-FSP sample. The WAAM-FSP samples have a larger number density of spot-like particles as compared to the WAAM samples due to the fragmentation as well as partially dissolution of second-phase particles caused by the violent stirring action and intense deformation of FSP. Both strengths and elongations of the manufactured Al–Cu alloy are enhanced by interlayer FSP, which is mainly ascribed to the combined action of porosity reduction, grain refinement, fragmentation and dissolution of the second-phase particles caused by interlayer FSP. The present study can provide theoretical guidance for the fabrication of Al-based alloy components with high performance using hybrid WAAM-FSP technique.